2021
DOI: 10.1155/2021/6618407
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Fly‐Ash‐Based Geopolymer Concrete by Gene Expression Programming and Random Forest

Abstract: Fly ash (FA) is a residual from thermal industries that has been effectively utilized in the production of FA-based geopolymer concrete (FGPC). To avoid time-consuming and costly experimental procedures, soft computing techniques, namely, random forest regression (RFR) and gene expression programming (GEP), are used in this study to develop an empirical model for the prediction of compressive strength of FGPC. A widespread, reliable, and consistent database of compressive strength of FGPC is set up via a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 95 publications
2
49
0
2
Order By: Relevance
“…According to Carrillo et al [ 67 ], a strong correlation between the experimental data and predicted results is achieved when the R value is between 0.8 and 1, while a moderate correlation is obtained if the R value ranges between 0.5 and 0.8. This was also in line with another study reported by Khan et al [ 68 ]. Moreover, close relationships between the experimental and estimated data have been proven with correlation values of 0.8–0.9 in many previous studies.…”
Section: Resultssupporting
confidence: 93%
“…According to Carrillo et al [ 67 ], a strong correlation between the experimental data and predicted results is achieved when the R value is between 0.8 and 1, while a moderate correlation is obtained if the R value ranges between 0.5 and 0.8. This was also in line with another study reported by Khan et al [ 68 ]. Moreover, close relationships between the experimental and estimated data have been proven with correlation values of 0.8–0.9 in many previous studies.…”
Section: Resultssupporting
confidence: 93%
“…However, the decision tree with bagging gives precise performance than an individual one, as illustrated in Figure 6d. This is due to an increase in model efficiency as it takes several data to train the best model by using weak base learners [47]. The ensemble model is optimized by making 20 sub-models, as depicted in Figure 6c.…”
Section: Decision Tree/ensemble Modelmentioning
confidence: 99%
“…Meanwhile, the experimental research on the compressive-shear mechanical properties of rubber fiber concrete has not been reported in the relevant literature, and therefore, a huge amount of test data is needed in the future to support the research in this aspect. e follow-up research shall carry out further experimental research on the shear mechanical properties of rubber fiber concrete by considering more influencing factors such as rubber particle content, fiber content, and axial compression ratio, so as to provide a direct basis for predicting the shear stress of rubber fiber concrete by applying machine learning [33].…”
Section: Failure Criterion Of Octahedral Stress Spacementioning
confidence: 99%